Upaya Meningkatkan Kepercayaan Diri Remaja Putri melalui Bimbingan Kelompok di Panti Asuhan Hanifa Jorong 3 Kampung Nagari Gadut Tilatang Kamang Kabupaten Agam - Jannah, Nadila Miftahul; Syawaluddin, Syawaluddin (Lembaga Yasin AlSys, 2023)
Group guidance is the provision of services in a group atmosphere by utilizing group dynamics. In the implementation of this group guidance activity, it can be seen how the efforts to increase the self-confidence of young women as foster children who are in the Orphanage. This study aims to (1) describe self-confidence, (2) describe group guidance, (3) and reveal efforts to increase girls’ self-confidence through group guidance. This type of research is qualitative research using observation and interview methods of the orphanage administrators, foster mothers and foster children who are in the orphanage. The data that has been collected from the informant is then carried out data reduction and data verification regarding efforts to increase the confidence of young women through group guidance at the Hanifa Jorong 3 Orphanage, Kampung Nagari Gadut, Tilatang Kamang, Agam Regency. With this group guidance activity it can help increase the confidence of the foster children in this orphanage.